Metodologia para la determinacion del costo por estudiante de contabilidad en la modalidad presencial y su incidencia en las finanzas de la uladech catolica – chimbote periodo 2010- 2011 - Gonzáles Rentería, Yuri Gagarin (2013)
This research aims to determine the cost per student of Accounting at the modality and its impact on the finances of the Catholic ULADECH Chimbote, period 2010-2011. The population consisted of the areas involved in the Financial Division of the Catholic ULADECH Chimbote and the sample by the Logistics area, area of Budget and Accounting area. The method used was the inductive-deductive, the Analytic - systemic, descriptive - and Quantitative. This methodology presents a cost structure based on the determination of direct material and / or supplies, labor and other service costs incurred by the institution during an academic semester consists of 17 weeks. There are identified all inductors and determine the values to be considered in the methodology. Established inductors automate the institution in the each of the elements of the proposed cost. This affects the ULADECH Catholic financially, since it allows to know the true cost and inductors incurred by identifying those which are necessary and critical to the learning process.